Seed dispersal and frugivory: ecology, evolution and conservation. Third International Symposium-Workshop on Frugivores and Seed Dispersal, São Pedro, Brazil, 6-11 August 2000 - Levey, D. J.; Galetti, M.; Galetti, M.; Levey, D. J.; Silva, W. R.; Silva, W. R. (Wallingford :CABI Publishing, 2002)
This book provides information on the historical and theoretical perspectives of biodiversity and ecology in tropical forests, plant and animal behaviour towards seed dispersal and plant-animal interactions within forest communities, consequences of seed dispersal, and conservation, biodiversity and management.
Keywords: KK100 - Forests and Forest Trees (Biology and Ecology); PP720 - Biological Resources (Plant); YY500 - Behaviour (Wild Animals), (New March 2000); ZZ331 - Plant Ecology; ZZ332 - Animal Ecology